Porang (Amorphophallus muelleri B.) Indirect Organogenesis - Nur Khozin, Mohammad; Ahmad Iqbal Rananda; Didik , Pudji Restanto (BIOVALENTIA: Biological Research Journal, 2024)
Organogenesis is regeneration mechanism on the process of organ formation derived from somatic or non-meristematic tissue on in vitro technique. Organogenesis can occur directly or indirectly. This research used porang leaves as explant, and medium MS Basal with addition such as sucrose, agar, combination of PGR’s 2,4 D and NAA, and aquadest. This research method used the Completely Randomize Design (CRD) with 9 different level combination of 2,4 D and NAA such as 2,0 ppm 2,4 D + 1,5 ppm NAA (A1), 2,0 ppm 2,4 D + 2,0 ppm NAA (A2), 2,0 ppm 2,4 D + 2,5 ppm NAA (A3), 2,5 ppm 2,4 D + 1,5 ppm NAA (A4), 2,5 ppm 2,4 D + 2,0 ppm NAA (A5), 2,5 ppm 2,4 D + 2,5 ppm NAA (A6), 3,0 ppm 2,4 D + 1,5 ppm NAA (A7), 3,0 ppm + 2,0 ppm NAA (A8), 3,0 ppm 2,4 D + 2,5 ppm NAA (A9) with 3 repetitions for each combination. Quantitative data such as the percentage of explants that appeared callus and roots were tested statistically by using ANOVA to determine the significance of the effect of the treatment. Treatments that had significant results were then tested using the DMRT test with a level of α=5%. Qualitative data were observed visually and analyzed descriptively. Combination concentration treatment of 2,4 D and NAA have the significant effect on callus and root formation. The level of 2 ppm 2,4 D and 2 ppm NAA is the best treatment on callus formation process in terms of 100% callus emerge and the early day appears at 24 days after planting and the best treatment on the process of root formation in terms of percentage roots emerge 100% and the early day roots appears at 46 days after planting. Indirect organogenesis is type of of root regeneration.